2020
DOI: 10.21203/rs.3.rs-26188/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Risk factors for severity of thrombocytopenia in full term infants: a single center study

Abstract: Background: Neonatal thrombocytopenia (NT) (platelet count <150 x 109/L) is a common finding in the neonatal intensive care unit (NICU). The main aim of this study was to assess the prevalence, rick factors, and outcomes of severe NT in full term (FT) infants.Methods: During the study period, all FT infants who met the inclusion criteria for NT on two occasions were included. Maternal data, such as maternal age, weight, gestational age, mode of delivery, and history of systemic diseases, including diabetes … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 2 publications
2
4
0
Order By: Relevance
“…GA and BW were not negatively associated with the incidence of severe thrombocytopenia, as mentioned in previous studies [4,5,11]. Sepsis is the most frequent cause of thrombocytopenia, as reported in several studies [16,17]. The higher incidence of total hemorrhage in neonates with severe thrombocytopenia discovered in our study was similar to that reported in the literature [10].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…GA and BW were not negatively associated with the incidence of severe thrombocytopenia, as mentioned in previous studies [4,5,11]. Sepsis is the most frequent cause of thrombocytopenia, as reported in several studies [16,17]. The higher incidence of total hemorrhage in neonates with severe thrombocytopenia discovered in our study was similar to that reported in the literature [10].…”
Section: Discussionsupporting
confidence: 90%
“…2 The lowest platelet counts in neonates with and without bleeding during study. Lines represent median with interquartile ranges incidence of IVH was consistent with the findings of Bolat et al [7] and Saber et al [16]. However, it remains uncertain whether thrombocytopenia causes IVH before the occurrence of thrombocytopenia [4,5].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Damage to vascular endothelium caused by bacteria is repaired by PLTs, resulting in increased platelet consumption, activated immune system, and promoted PLT apoptosis 33 . Other common viral infections, such as Torch or fungal infection, directly destroy the megakaryocytes or PLTs, inhibit bone marrow hematopoiesis, induce the production of autoantibodies to accelerate PLT destruction and affect their levels in peripheral blood.…”
Section: Correlation Between Plt Activation Indicators and Nec Occurrencementioning
confidence: 99%
“…3 Development of TCP among neonates is complex and depends upon various maternal and fetal conditions. 4 Most commonly linked conditions with TCP are sepsis, birth asphyxia, low birth-weight (LBW), prematurity, necrotizing colitis, exchange transfusion while maternal factors include hypertension and idiopathic thrombocytopenic purpura. 5 Sepsis is found to be the commonest cause of TCP and it aggravates within 24 to 48 hours following the infective process.…”
Section: Introductionmentioning
confidence: 99%